Comparison of pipelle endometrial sampling with Dilatation and Curettage among patients with abnormal uterine bleeding at a tertiary care hospital - Iqbal, Tabia; Rizvi, Syed Masuma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Abnormal uterine bleeding is a common debilitating condition and may be due to benign as well as malignant causes. Management relies on histological evaluation of endometrial sample obtained via biopsy. The aim of this study was to compare pipelle endometrial sampling with traditional dilatation and curettage. Methods: This was a cross-sectional study involving 45 patients over the age of 40 years. Endometrial sampling was performed by the Pipelle device followed by D&C and samples were sent to a pathologist, who was blinded to the methods of sampling for histopathology assessment. The histopathology reports of the Pipelle sample were compared with that of the D&C sample and the D&C report was considered as the gold standard. Results: 97.8% of the samples obtained by conventional D&C, while 95.6% of the samples obtained by the Pipelle device were adequate for histopathological examination. The most common finding in both Pipelle sampling and D&C was proliferative endometrium followed by secretory and disordered endometrium. Polyp was only picked up by D&C, whereas the Pipelle sampling failed to do so. Failure of obtaining a sample was reported in 4.4% of the patients in Pipelle sampling whereas it was 2.2% in D&C. Adenocarcinoma was seen in two patients and it was picked by both D&C and Pipelle sampling. Conclusions: Endometrial sampling using Pipelle is an accessible and safe method for outpatient tissue diagnosis, providing a cost-effective alternative to D&C.